Identification of Cardiovascular Risk Factors in Obese Adolescents With Metabolic Syndrome - Lee, Jung Won; Hong, Young Mi; Kim, Hae Soon (Frontiers in Pediatrics, 2021)
Objective: There are studies that show different associations between metabolic syndrome (MS) and cardiovascular disease in adolescent. This study is aimed to identify cardio-vascular risk factors in obese adolescents with MS. Methods: Sixty-five obese adolescents with a body mass index (BMI) > 95 percentile were enrolled and divided into two groups with MS or without MS. Left ventricular mass index (LVMI), ejection fraction (EF), epicardial fat thickness (EFT), visceral fat thickness (VFT) and carotid intima-media thickness (CIMT) were measured. Anthropometric and blood chemistry parameters were estimated. Above parameters were compared based on presence or absence of MS. Results: The prevalence of MS was 23.1% in obese adolescents. LVMI showed significant correlation with BMI, hip circumference (HC), fat mass, obesity index (OI), insulin, homeostasis model assessment of insulin resistance (HOMA-IR), total cholesterol (TC), LDL-cholesterol (LDL-C) and waist circumference (WC). VFT significantly correlated with WC, BMI, HC, OI, fat %, fat mass, insulin, TC, LDL-C, insulin, TG, glucose, HOMA-IR and leptin. Conclusions: Screening for the MS in overweight adolescents may help to prevent cardiovascular disease. These data suggest that LVMI and VFT are significant parameters for predicting cardiovascular disease risk in obese adolescents.